Strategies of participle agreement with conjoined subjects in Bosnian/Croatian/Serbian - Leko, Nedžad (Linguistica (Ljubljana), 2016)
In this paper, we demonstrate that Bosnian/Croatian/Serbian (BCS), like Slovenian, has three distinct strategies of subject-predicate agreement when the subject consists of conjoined noun phrases: 1. agreement with the maximal projection - a Boolean Phrase (&P), 2. agreement with the conjunct which is closest to the participle, and 3. agreement with the conjunct which is hierarchically the highest. In order to test the initial hypothesis that there are three agreement strategies, we conducted a controlled experimental study of the morphosyntax of agreement between conjoined subjects and participles in BCS, which consisted of an oral production experiment and a written production experiment. These experiments revealed a high presence of default agreement and closest conjunct agreement in the language. 50% of preverbal conjoined phrases elicited the default masculine agreement and 95% of postverbal conjoined noun phrases elicited the closest conjunct agreement. However, the bulk of the analysis focused on the possibility of treating the highest conjunct agreement (HCA) as a legitimate agreement strategy. 7% of all of the agreement forms in the subject preverbal (SV) examples demonstrated HCA. These figures increased to 13% if individual conditions were considered. Last conjunct agreement (LCA) for subject postverbal (VS) examples, on the other hand, was only present in 1% of the examples. For this reason, we classified them as performance errors and refuted LCA as an agreement strategy. These results are contrary to Bošković%s findings (2009), in which he does not acknowledge HCA as a legitimate strategy, however, our results do confirm the findings of Marušič et al. (2015).
Keywords: accord (linguistique); bosanščina; bosnien; croate; Croatian; deležnik; eksperimentalna skladnja; hrvaščina; morphologie; oblikoslovje; osebek; participe; povedek; prédicat; serbe; skladnja; srbščina; sujet; syntax; syntaxe; syntaxe expérimentale; ujemanje (jezikoslovje)